High Frequency Vibrations Impact on Mechanical Properties of Nanocrystalline Titanium - Bakai, S.А.; Smolianets, R.V.; Kovtun, K.V.; Moskalenko, V.А.; Bakai, A.S. (Металлофизика и новейшие технологии, 2016)
Mechanical properties of nanocrystalline titanium are studied under uniform confined compression with ultrasound oscillations of 20 kHz to clarify the way of high-frequency vibrations’ effect on mechanical properties of nanocrystals. The nanocrystalline VT1-0 titanium of commercial purity used in the experiments is fabricated employing cryogenic grain-fragmentation technique. This material has a broad distribution in grain size (20—80 nm) with the average size amounting to 40 nm. The amplitude of cyclic stress approaches 275 МРа. The high-frequency vibrations are found to lower the yield stress and to initiate the formation of shear bands. With the deformation rate of 10⁻⁴ s⁻¹, the yield stress becomes 2.5 times lower, and the major shear band forms under the deformation of 0.11 that is 5.7 times lower than the true deformation before the major shear band formation without action of the vibrations. On increasing the deformation rate up to 10⁻³ s⁻¹, the consequences of high-frequency vibrations’ impact are weaken substantially. Для з’ясування питання про вплив високочастотних вібрацій на механічні властивості нанокристалів виконано дослідження механічних властивостей нанокристалічного титану при однорідному тривісному стисканні під дією ультразвукових коливань із частотою у 20 кГц. Використаний в експериментах нанокристалічний титан промислової чистоти ВТ1-0 одержано методом кріогенної фраґментації зерен. Цей матеріял має широкий розподіл зерен за розмірами (20—80 нм) із середнім розміром біля 40 нм. Амплітуда циклічних напружень сягала 275 МПа. Встановлено, що високочастотні вібрації знижують поріг пластичности й ініціюють утворення катастрофічних смуг зсуву. За швидкости деформації у 10⁻⁴ с⁻¹ поріг пластичности під дією вібрацій знижується в 2,5 рази, а катастрофічна смуга зсуву утворюється при деформації 0,11, яка є у 5,7 разів нижчою, ніж істинна деформація до моменту утворення катастрофічної смуги зсуву без дії вібрацій. При збільшенні швидкости деформації до 10⁻³ с⁻¹ ефекти дії високочастотних вібрацій істотно послаблюються. Для выяснения вопроса о влиянии высокочастотных вибраций на механические свойства нанокристаллов выполнены исследования механических свойств нанокристаллического титана при однородном трёхосном сжатии под действием ультразвуковых колебаний с частотой 20 кГц. Использованный в экспериментах нанокристаллический титан промышленной чистоты ВТ1-0 получен методом криогенной фрагментации зёрен. Этот материал имеет широкое распределение зёрен по размерам (20—80 нм) со средним размером, равным 40 нм. Амплитуда циклических напряжений достигала 275 МПа. Установлено, что высокочастотные вибрации снижают порог пластичности и инициируют образование катастрофических полос сдвига. При скорости деформации 10⁻⁴ с−1 порог пластичности под действием вибраций снижается в 2,5 раза, а катастрофическая полоса сдвига образуется при деформации 0,11, которая в 5,7 раза ниже, чем истинная деформация до момента образования катастрофической полосы сдвига без воздействия вибраций. При увеличении скорости деформации до 10⁻³ с⁻¹ эффекты воздействия высокочастотных вибраций существенно ослабляются.